Functional assessment of tandem coronary artery stenosis by intracoronary optical coherence tomography-derived virtual fractional flow reserve: a case series. Issue 2 (24th May 2019) - Okuya, Yoshiyuki; Seike, Fumiyasu; Yoneda, Kohei; Takahashi, Takefumi; Kishi, Koichi; Hiasa, Yoshikazu
Abstract: Background: Optical coherence tomography (OCT)-derived fractional flow reserve (FFR)—which may be calculated using fluid dynamics—demonstrated an excellent correlation with the wire-based FFR. However, the applicability of the OCT-derived FFR in the assessment of tandem lesions is currently unclear. Case summary: We present two cases of tandem lesions in the mid segment of the left anterior descending (LAD) artery which could have assessed accurately by OCT-derived FFR. The first patient underwent wire-based FFR at the far distal site of LAD, showed a value of 0.66. The OCT-derived FFR was calculated, yielding a value of 0.64. In the absence of stenosis at the proximal lesion, the OCT-derived FFR was calculated as 0.79, which was as same as the wire-based FFR obtained after stenting to the proximal lesion. Thus, additional stenting was performed at the distal lesion. The second patient underwent wire-based FFR at the far distal site of LAD, showed a value of 0.76 which was as same vale as OCT-derived FFR. Considering the absence of stenosis in the proximal lesion, the OCT-derived FFR was estimated as 0.88. After coronary stenting in the proximal lesion, the wire-based FFR yielded a value of 0.90. Therefore, additional intervention to the distal lesion was deferred. Discussion: The described reports are the first two cases which performed physiological assessment using OCT in tandem lesions. The OCT-derived FFR might be able to estimate the wire-based FFR and the severity of each individual lesion in patients with tandem lesions.